What do popular Spanish women's magazines say about caesarean section? A 21‐year survey. (28th January 2014) - Torloni, MR; Campos Mansilla, B; Merialdi, M; Betrán, AP
<x xml:space="preserve">Abstract</x> Objectives Caesarean section (CS) rates are increasing worldwide and maternal request is cited as one of the main reasons for this trend. Women's preferences for route of delivery are influenced by popular media, including magazines. We assessed the information on CS presented in Spanish women's magazines. Design Systematic review. Setting Women's magazines printed from 1989 to 2009 with the largest national distribution. Sample Articles with any information on CS. Methods Articles were selected, read and abstracted in duplicate. Sources of information, scientific accuracy, comprehensiveness and women's testimonials were objectively extracted using a content analysis form designed for this study. Main outcome measures Accuracy, comprehensiveness and sources of information. Results Most (67%) of the 1223 selected articles presented exclusively personal opinion/birth stories, 12% reported the potential benefits of CS, 26% mentioned the short‐term and 10% mentioned the long‐term maternal risks, and 6% highlighted the perinatal risks of CS. The most frequent short‐term risks were the increased time for maternal recovery (n = 86), frustration/feelings of failure (n = 83) and increased post‐surgical pain (n = 71). The most frequently cited long‐term risks were uterine rupture (n = 57) and the need for another CS in any subsequent pregnancy (n = 42). Less than 5% of the selected articles reported that CS could increase the risks of infection (n = 53), haemorrhage (n = 31) or placenta praevia/accreta in future pregnancies (n = 6). The sources of information were not reported by 68% of the articles. Conclusions The portrayal of CS in Spanish women's magazines is not sufficiently comprehensive and does not provide adequate important information to help the readership to understand the real benefits and risks of this route of delivery.